Integrated β-catenin, BMP, PTEN, and Notch signalling patterns the nephron - Lindström, Nils O; Lawrence, Melanie L; Burn, Sally F; Johansson, Jeanette A; Bakker, Elvira RM; Ridgway, Rachel A; Chang, C-Hong; Karolak, Michele J; Oxburgh, Leif; Headon, Denis J; Sansom, Owen J; Smits, Ron; et al. (eLife, 2015)
The different segments of the nephron and glomerulus in the kidney balance the processes of water homeostasis, solute recovery, blood filtration, and metabolite excretion. When segment function is disrupted, a range of pathological features are presented. Little is known about nephron patterning during embryogenesis. In this study, we demonstrate that the early nephron is patterned by a gradient in β-catenin activity along the axis of the nephron tubule. By modifying β-catenin activity, we force cells within nephrons to differentiate according to the imposed β-catenin activity level, thereby causing spatial shifts in nephron segments. The β-catenin signalling gradient interacts with the BMP pathway which, through PTEN/PI3K/AKT signalling, antagonises β-catenin activity and promotes segment identities associated with low β-catenin activity. β-catenin activity and PI3K signalling also integrate with Notch signalling to control segmentation: modulating β-catenin activity or PI3K rescues segment identities normally lost by inhibition of Notch. Our data therefore identifies a molecular network for nephron patterning.
Keywords: kidney development; patterning; beta-catenin; PI3K; Notch; BMP